#TITLE_ALTERNATIVE# - RANDI FARMANA PUTRA (NIM : 10207066); Pembimbing 1 : Dr. Nurhasan; Pembimbing 2 : Dr. rer. nat Spa
Papandayan volcano is an active volcano at Garut Regency, West Java. The most recent large eruption occured in 2002. There are some geophysical method that can be used to observe subsurface of the earth include magnetic method. In this final project magnetic method is used to determine distribution of subsurface magnetic field that can be linked to the distribution of temperature. Magnetic field data acquisition has been done around Papandayan volcanoÃ‚Â’s craters in an area about 400m2 wide using Proton Precision Magnetometer G-856AX. Magnetic field data are corrected using diurnal correction and IGRF correction in order to obtain the value of magnetic anomaly which is used as basis for estimating under surface temperature distribution. Based on magnetic field distribution map, known that the northern part of the survey area has a smaller magnetic field value than the southern part which indicates the northern part has higher temperature than the southern part. Based on forward modeling results, we get magnetic body models which have rectangular form with length, depth, angle, susceptibility as parameters. We obtain two kind of rock susceptibility 0.0135 and 0.18 which are interpreted as andesite and basaltic rock. We use geo-electric data as supporting data for interpreting the results.